Ryanodine receptor point mutations confer diamide insecticide resistance in tomato leafminer, Tuta absoluta (Lepidoptera: Gelechiidae). (January 2017) - Roditakis, Emmanouil; Steinbach, Denise; Moritz, Gerald; Vasakis, Emmanouil; Stavrakaki, Marianna; Ilias, Aris; García-Vidal, Lidia; Martínez-Aguirre, María del Rosario; Bielza, Pablo; Morou, Evangelia; Silva, Jefferson E.; Silva, Wellington M.; et al.
Abstract: Insect ryanodine receptors (RyR) are the molecular target-site for the recently introduced diamide insecticides. Diamides are particularly active on Lepidoptera pests, including tomato leafminer, Tuta absoluta (Lepidoptera: Gelechiidae). High levels of diamide resistance were recently described in some European populations of T. absoluta, however, the mechanisms of resistance remained unknown. In this study the molecular basis of diamide resistance was investigated in a diamide resistant strain from Italy (IT-GELA-SD4), and additional resistant field populations collected in Greece, Spain and Brazil. The genetics of resistance was investigated by reciprocally crossing strain IT-GELA-SD4 with a susceptible strain and revealed an autosomal incompletely recessive mode of inheritance. To investigate the possible role of target-site mutations as known from diamondback moth ( Plutella xylostella ), we sequenced respective domains of the RyR gene of T. absoluta. Genotyping of individuals of IT-GELA-SD4 and field-collected strains showing different levels of diamide resistance revealed the presence of G4903E and I4746M RyR target-site mutations. These amino acid substitutions correspond to those recently described for diamide resistant diamondback moth, i.e. G4946E and I4790M. We also detected two novel mutations, G4903V and I4746T, in some of the resistant T. absoluta strains. Radioligand binding studies with thoracic membrane preparations of the IT-GELA-SD4 strain provided functional evidence that these mutations alter the affinity of the RyR to diamides. In combination with previous work on P. xylostella our study highlights the importance of position G4903 (G4946 in P. xylostella ) of the insect RyR in defining sensitivity to diamides. The discovery of diamide resistance mutations in T. absoluta populations of diverse geographic origin has serious implications for the efficacy of diamides under applied conditions. The implementation of appropriate resistance management strategies is strongly advised to delay the further spread of resistance. Graphical abstract: Highlights: Diamides are major weapon against Tuta absoluta; however, resistance evolved. Diamide resistance has an autosomal incompletely recessive mode of inheritance. Known and novel alternative RyR mutations were associated with the phenotype. Radioligand binding: these mutations alter the affinity of the RyR to diamides. Diamide resistance mutations are present in T. absoluta populations worldwide.